The Bangkok Treaty Of 1909 As The Beginning To Britishdomination In The Northern Malay States: A Literature Review - Muhammad Zharif Baharudin; Izziah Suryani Mat Resad; Mohamad Zulfazdlee Abul Hassan Ashari; Ezad Azraai Jamsari; Adibah Sulaiman @ Mohamad (Jana Publication and Research LLP, 2025)
Non Indexed Publication (Tier 4)